Procedural and Tactical Problems of Examination as Investigative Actions in RA Criminal Procedure - Chakhoyan, A.; Martirosyan, A. (Bulletin of Yerevan University C: Jurisprudence, 2019)
Procedural and tactical problems of examination, one of the investigative actions provided by RA code of criminal procedure, are discussed in the paper presented. Almost all the problematic issues concerning the aims of the examination and the procedural order of its execution are raised in the frames of the presented paper. The specialty of this paper is that the authors studied not only the relevant articles of RA Code of Criminal Procedure, which provide legal grounds for the discussed investigative action but also covered a number of practical problems arising due to the lack of legal regulation. The authors have gone beyond the identification of the shortcomings of the code of criminal procedure and suggested possible solutions for overcoming the highlighted problems and increasing the effectiveness of the investigation.
Keywords: investigative action, examination, traces of crime, injury, special signs, examination of clothes and shoes, forensic medical examination, technical means